Land Dispute Resolution Due to the Issuance of Double Certificates by the National Land Agency - Harniwati; Engrina Fauzi; Fauzan Zakir; Miasiratni; Uci Asriadi (Master of Law Program, Ekasakti University, 2026)
Land as one of the human needs has a very important role in the basis of human life. The term agrarian itself in Indonesia refers to Law Number 5 of 1960 concerning Basic Agrarian Regulations, hereinafter known as UUPA. Based on the provisions of Article 1 paragraph (2) of UUPA, it states that the words